2023
DOI: 10.1038/s41598-023-36511-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the reasonable proportions of rock-like materials for water-induced strength degradation in rock slope model test

Abstract: Water-induced strength deterioration of rock mass is a crucial factor for rock slope instability. To better show the degradation process of rock slope water–rock interaction, we used bentonite as a water-sensitive regulator to build a new rock-like material that matches the features of water-induced strength degradation based on the cement-gypsum bonded materials. Twenty-five schemes of the material mixture proportion were designed using the orthogonal design method considering four factors with five variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(34 reference statements)
2
0
0
Order By: Relevance
“…Moreover, the analysis in Table 5 reveals that the largest range of elastic modulus is observed under different levels of factor A, which measures 0.11. Cui et al [36] found that the elastic modulus of rock-like materials decreases with the ratio of aggregate and binder and that this ratio has the most significant effect on elastic modulus, which is consistent with the pattern presented in this paper. This indicates that factor A has the greatest degree of influence on the elastic modulus, and there is a negative correlation between the elastic modulus and the level of factor A. et al [36] found that the elastic modulus of rock-like materials decreases with the ratio of aggregate and binder and that this ratio has the most significant effect on elastic modulus, which is consistent with the pattern presented in this paper.…”
Section: Analysis Of Factors' Sensitivity To Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the analysis in Table 5 reveals that the largest range of elastic modulus is observed under different levels of factor A, which measures 0.11. Cui et al [36] found that the elastic modulus of rock-like materials decreases with the ratio of aggregate and binder and that this ratio has the most significant effect on elastic modulus, which is consistent with the pattern presented in this paper. This indicates that factor A has the greatest degree of influence on the elastic modulus, and there is a negative correlation between the elastic modulus and the level of factor A. et al [36] found that the elastic modulus of rock-like materials decreases with the ratio of aggregate and binder and that this ratio has the most significant effect on elastic modulus, which is consistent with the pattern presented in this paper.…”
Section: Analysis Of Factors' Sensitivity To Parameterssupporting
confidence: 92%
“…Cui et al [36] found that the elastic modulus of rock-like materials decreases with the ratio of aggregate and binder and that this ratio has the most significant effect on elastic modulus, which is consistent with the pattern presented in this paper. This indicates that factor A has the greatest degree of influence on the elastic modulus, and there is a negative correlation between the elastic modulus and the level of factor A. et al [36] found that the elastic modulus of rock-like materials decreases with the ratio of aggregate and binder and that this ratio has the most significant effect on elastic modulus, which is consistent with the pattern presented in this paper. This indicates that factor A has the greatest degree of influence on the elastic modulus, and there is a negative correlation between the elastic modulus and the level of factor A.…”
Section: Analysis Of Factors' Sensitivity To Parameterssupporting
confidence: 92%